PENGEMBANGAN E-MARKETPLACE UMKM BERBASIS WEB DENGAN SISTEM REKOMENDASI PRODUKMENGGUNAKAN METODE SAW DI KOTA PANGKALPINANG - Erik Erik; Ade Septryanti (Information System Journal, 2026)
Micro, Small, and Medium Enterprises (MSMEs) play a strategic role in the economy of Pangkalpinang City, however limited digital technology adoption remains a major obstacle. This study designs and implements a web-based e-marketplace with a product recommendation system using the Simple Additive Weighting (SAW) method. Weights were determined through a survey of 50 respondents, yielding four criteria: Price (W=26.4%), Rating (W=25.2%), Popularity (W=25.0%), and Distance (W=23.4%). The system was developed using Laravel 11 with MVC architecture and Bootstrap 5. Black-box testing on 48 scenarios showed 95.8% success. Accuracy evaluation yielded Precision 89.4%, Recall 85.8%, and F1-Score 87.6%. System Usability Scale (SUS) testing with 50 users produced an average score of 81.4 (Good category).